2023
DOI: 10.1101/2023.01.02.522449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composition of nasopharyngeal microbiota in individuals with SARS-CoV-2 infection across three COVID-19 waves in India

Abstract: Background: SARS-COV-2 is an enveloped RNA virus that is responsible for the global pandemic COVID-19. The virus is reported to cause dysbiosis of the Human Nasopharyngeal microbiota, consequently regulating the host immunity and infection pathophysiology. The compositional change in microbial diversity due to the virus has been reported by independent authors in smaller cohorts and different geographical regions, with a few correlating with fungal and bacterial co-infections. Here, we study for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID-19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response. [83][84][85] 3. 1.3 Changes in microbiota and immune microenvironment SARS-CoV-2 infection is associated with intestinal inflammation, intestinal barrier disruption, and changes in lipid metabolism.…”
Section: Changes In the Microbiota Of The Upper Respiratory Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID-19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response. [83][84][85] 3. 1.3 Changes in microbiota and immune microenvironment SARS-CoV-2 infection is associated with intestinal inflammation, intestinal barrier disruption, and changes in lipid metabolism.…”
Section: Changes In the Microbiota Of The Upper Respiratory Tractmentioning
confidence: 99%
“…Nasopharyngeal microbiota may be associated with SARS‐CoV‐2 infection. Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID‐19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response 83–85 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%